Inside Front Cover: Label‐free bacterial colony detection and viability assessment by continuous‐wave terahertz transmission imaging (J. Biophotonics 8/2018). Issue 8 (8th August 2018) - Yang, Xiang; Shi, Jia; Wang, Yuye; Yang, Ke; Zhao, Xiang; Wang, Guiyu; Xu, Degang; Wang, Yunxia; Yao, Jianquan; Fu, Weiling
Abstract : A rapid, simple and one‐step method for analyzing bacterial colonies was proposed using a continuous‐wave terahertz (THz) imaging system in this study. The distribution of mixed bacterial colonies has been detected, and the target bacterium could also be easily recognized in mixed samples. The results clearly demonstrate the potential usage of THz imaging for bacterial colony sensing in a label‐free and nondestructive manner. Further details can be found in the article by Xiang Yang, Jia Shi, Yuye Wang et al. (e201700386 ). Abstract : A rapid, simple and one‐step method for analyzing bacterial colonies was proposed using a continuous‐wave terahertz (THz) imaging system in this study. The distribution of mixed bacterial colonies has been detected, and the target bacterium could also be easily recognized in mixed samples. The results clearly demonstrate the potential usage of THz imaging for bacterial colony sensing in a label‐free and nondestructive manner. Further details can be found in the article by Xiang Yang, Jia Shi, Yuye Wang et al. (e201700386 ).